2011
DOI: 10.1002/j.1551-8833.2011.tb11459.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of variability in radionuclide measurements in drinking water

Abstract: A blind interlaboratory study of radium‐226 (Ra‐226), radium‐228 (Ra‐228), and gross alpha and beta activity was conducted among five multistate certified laboratories to examine concerns regarding analytical variability for compliance with the revised Radionuclides Rule. Results of the interlaboratory study demonstrated that although Ra‐226 and gross beta measurements appeared to be both accurate and precise, even at low levels, Ra‐228 and gross alpha measurements were much less robust both within and among l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…The results obtained from this ILC of Site groundwater and surface water samples are generally consistent with the findings from the prior 2011 study [5] with respect to observed variability in 226 Ra compared to 228 Ra. The current ILC indicate that 228 Ra data reported by the existing contract laboratory (Lab A) are biased high relative to those reported by Lab B, Lab C, Lab D, and this may be due to differences in laboratory skill and technique among the various laboratory technicians [5]. However, the resulting upward trends in 228 Ra/ 226 Ra ratios (observed in both impacted wells and the background location) after the 228 Ra method was changed from 904.0 to Ra-05 are more difficult to explain.…”
Section: Conclusion and Recommendationssupporting
confidence: 86%
See 3 more Smart Citations
“…The results obtained from this ILC of Site groundwater and surface water samples are generally consistent with the findings from the prior 2011 study [5] with respect to observed variability in 226 Ra compared to 228 Ra. The current ILC indicate that 228 Ra data reported by the existing contract laboratory (Lab A) are biased high relative to those reported by Lab B, Lab C, Lab D, and this may be due to differences in laboratory skill and technique among the various laboratory technicians [5]. However, the resulting upward trends in 228 Ra/ 226 Ra ratios (observed in both impacted wells and the background location) after the 228 Ra method was changed from 904.0 to Ra-05 are more difficult to explain.…”
Section: Conclusion and Recommendationssupporting
confidence: 86%
“…Lab A also reported the highest measured 228 Ra concentration of all field blanks (2 pCi/L), and consequently those data for total 228 Ra were qualified as estimated with high bias. A prior study relating to radionuclide variability in water samples [5] showed that radionuclide activity in groundwater can vary up to four-fold due to seasonal effects, but also noted that the variability could reflect issues related to method and laboratory variability. The greatest source of error for 226 Ra is counting uncertainty, but the overall accuracy and precision for 226 Ra results was acceptable among various laboratories.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For 228 Ra, two of the laboratories used Method 904.0 (M904.0) (Labs B, C), while Lab A and Lab D used Method Ra-05. Each Ra method in Table 2 has been approved for drinking water compliance analysis by the USEPA and therefore should not produce significantly different results [6].…”
Section: Methodsmentioning
confidence: 99%